Use of zinc quantum dot biochar and AMF for alleviation of Cd stress in maize: Regulation of physiological and biochemical attributes - Mashael M. Alotibi; Nahaa M. Alotaibi; Ghulam Sabir Hussain; Shabir Hussain; Suleman Haider Shah; Adel M. Ghoneim; Khadim Dawar; Misbah Hareem (Plant Stress, 2023)
In different heavy metals, cadmium is one of the acute toxins. It also interferes with various physiological processes in plants, such as photosynthesis, respiration, and enzyme activity. To improve the growth of plants in Cd stress, arbuscular mycorrhizae can play an imperative role. On the other hand, the use of quantum dots technology is also gaining the attention of scientists. That's why the current study investigates the effectiveness of using zinc quantum dot biochar (ZQDB) and arbuscular mycorrhizal fungi (AMF) in alleviating cadmium (Cd) stress in maize plants. The results showed that AMF+ZQDB performed significantly best at the highest level of 5Cd (5mgCd/kg soil) for enhancement in plant height (28.20 %), shoot dry weight (48.78 %), chlorophyll a (32.45 %), chlorophyll b (44.03 %) and total chlorophyll (22.02 %) compared to control (NoAMF+NoZQDB). A significant enhancement in photosynthetic rate (12.95 %) and transpiration rate (39.99 %) concentration of carbon dioxide also validated the effectiveness of AMF+ZQDB over control (NoAMF+NoZQDB) at 5Cd. For photochemical quenching decrease was 25.1 %, 2.98 %, 20.7 %, and 20.3 %, respectively, compared to the control group at 5Cd where NoAMF+NoZQDB, AMF, ZQDB, and AMF+ZQDB treatments were applied. AMF+ZQDB treatment of 5Cd showed a 30.22 % decrease in electron transport rate and 34.67 % decrease in non-photochemical quenching compared to control (NoAMF+NoZQDB). In conclusion, AMF + ZQDB is an effective amendment for alleviating Cd stress in maize by regulating biochemical and physiological attributes. Further investigations are recommended at the field level using different crops to validate the effectiveness of AMF + ZQDB as a promising amendment for minimizing Cd toxicity.